Quasi‐Emulsion Confined Synthesis of Edge‐Rich Ultrathin MoS2 Nanosheets/Graphene Hybrid for Enhanced Hydrogen Evolution. Issue 3 (2nd November 2017) - Yin, Xuying; Yan, Ya; Miao, Mao; Zhan, Ke; Li, Pingwei; Yang, Junhe; Zhao, Bin; Xia, Bao Yu
Abstract: High‐purity hydrogen produced by water splitting is considered as one of the most promising fuels to replace traditional fossil fuels. Developing highly efficient electrocatalysts toward hydrogen evolution is vital for the realization of large‐scale H2 generation. Glycerol is used herein in a facile solvothermal process to synthesize edge‐rich ultrathin MoS2 /reduced graphene oxide (RGO) composites. The introduction of glycerol plays an important role in the formation of such interesting structures. The MoS2 /RGO electrocatalyst exhibits excellent hydrogen evolution reaction (HER) activity and remarkable stability, owing to the rich active edges and improved electrical conductivity of the catalyst composites. This work provides new insights to engineer the structures of MoS x ‐based composites and thus achieves more active and efficient electrocatalysts. Abstract : Slave to your emulsions : An edge‐rich ultrathin MoS2 /RGO hybrid is synthesized by a simple hydrothermal method in a glycerol generated quasi‐emulsion system. The resulting MoS2 /RGO hybrid delivers an excellent electrochemical catalytic activity and long‐term cycling stability towards hydrogen evolution reaction (HER).